Benefits of Patisiran on Functional Capacity in ATTR Cardiac Amyloidosis - John L. Berk, MD; Olivier Lairez, MD, PhD; Pedro Schwartzmann, MD, PhD; Shaun Bender, PhD; Matthew T. White, PhD; Patrick Y. Jay, MD, PhD; David Danese, MBA; Ronald Witteles, MD (JACC: Advances)
Background: Patients with transthyretin amyloidosis with cardiomyopathy (ATTR-CM) suffer substantial morbidity and mortality. The meaningful preservation of functional capacity and quality of life are important priorities. Objectives: The 6-minute walk test (6MWT), a measure of functional capacity, was the primary outcome in the APOLLO-B study of patisiran in patients with ATTR-CM; the treatment benefit vs placebo was +15 m over 12 months. We estimated the minimal clinically important difference for change in 6MWT performance. Methods: Change from baseline in 6MWT performance was anchored to established categories of clinically important change in the Kansas City Cardiomyopathy Questionnaire-Overall Summary score. To relate changes in 6MWT performance to activities of daily living, we fit a proportional-odds cumulative logit model for items in the Kansas City Cardiomyopathy Questionnaire Physical Limitation domain. Results: The APOLLO-B trial randomized 360 patients to receive placebo (n = 179) or patisiran (n = 181). The estimated minimal clinically important difference in 6MWT was 6.9 to 7.8 m. When comparing the change from baseline in 6MWT at month 12 between 2 patients, 15 m greater preservation was associated with approximately 10% to 16% lower odds of deterioration in walking 1 block (OR: 0.88 [95% CI: 0.83-0.93]), climbing stairs (OR: 0.84 [95% CI: 0.80-0.89]), hurrying/jogging (OR: 0.88 [95% CI: 0.83-0.93]), dressing oneself (OR: 0.85 [95% CI: 0.81-0.90]), and performing yard/housework or carrying groceries (OR: 0.89 [95% CI: 0.84-0.93]). Conclusions: In patients with ATTR-CM treated with patisiran, mean population-level differences of 7 to 8 m in 6MWT have practical relevance. The magnitude of the impact of patisiran on 6MWT performance over 12 months in APOLLO-B was associated with preserving the ability to perform activities of daily living.